2007
DOI: 10.3171/ped.2007.106.4.268
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following decompressive craniectomy in children with severe traumatic brain injury: a 10-year single-center experience with long-term follow up

Abstract: Although the mortality rate for children with severe TBI remains high, decompressive craniectomy is effective in reducing ICP and is associated with good outcomes in surviving patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
105
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 31 publications
8
105
3
3
Order By: Relevance
“…In a study of 23 patients younger than 19 years of age, Jagannathan et al reported that children with TBI who were treated with DC had a favorable outcome, with a mean GOS score of 4.2 at follow-up. 10 In a study of 14 children with severe TBI, Pérez Suárez et al also reported a favorable outcome, with a mean GOS score of 4.4 (range 4-5) at the 2-year follow-up. 17 In our study the majority of our patients who were treated with DC had a favorable GOS score.…”
Section: % (5/17mentioning
confidence: 99%
“…In a study of 23 patients younger than 19 years of age, Jagannathan et al reported that children with TBI who were treated with DC had a favorable outcome, with a mean GOS score of 4.2 at follow-up. 10 In a study of 14 children with severe TBI, Pérez Suárez et al also reported a favorable outcome, with a mean GOS score of 4.4 (range 4-5) at the 2-year follow-up. 17 In our study the majority of our patients who were treated with DC had a favorable GOS score.…”
Section: % (5/17mentioning
confidence: 99%
“…12,23,37 The renewed interest in decompressive craniectomy in the management of TBI is evidenced by 2 clinical trials currently underway-the RESCUEicp (Randomized Evaluation of Surgery for Uncontrollable Elevation of Intracranial Pressure) trial 19 and the DECRA (DEcompressive CRAniectomy) trial. 34 There have been several reports on decompressive craniectomy in children with TBI, 1,12,20,23,25,37 but few have specifically addressed its efficacy with nonaccidental or inflicted head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies including a recent report directly assessing the various methods have suggested the frontooccipital horn ratio may better serve as an estimate of ventricular volume in those for whom there is concern for hydrocephalus. 16 Pediatric patients with TBI can develop delayed hydrocephalus: 20% of patients with severe injuries, 13 29.5% after a decompressive craniectomy (accidental trauma), 7 and 40% of patients with pediatric TBI (accidental and nonaccidental trauma). 9 It's unclear from these studies what the natural history of developing hydrocephalus is in the NAHT population.…”
Section: Discussionmentioning
confidence: 99%